Sharia Policy and Its Impact on Achieving Food Security - Amer, Ibrahim Muhammad fandi Bani (Civilization Research: Journal of Islamic Studies, 2025)
This research aims to demonstrate the validity of Islamic law for all times and places, and to demonstrate the importance of having a guardian who is concerned with managing the affairs of the country, and supervising them in various aspects, and the keenness of Islamic law to preserve human life.I relied in writing this research on the inductive and analytical approach: by inducting and analyzing the legal texts in the Qur’an and Sunnah, and explaining the legal approach to achieving food security.The researcher concluded that Islamic law is capable of addressing the food security crisis, through the management and organization of the guardian of the country’s affairs, and its approach to achieving food security, as work is sacred in Islam, and striving for a livelihood is worship, and the legitimacy of zakat and charity, and the prohibition of usury, monopoly, and everything that may harm society.The researcher recommended that the guardian should personally supervise the achievement of food security, due to its importance in the stability of society, and that there should be special funds to support this sector.